2000
DOI: 10.1002/(sici)1098-2795(200001)55:1<55::aid-mrd8>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Kit ligand actions on ovarian stromal cells: Effects on theca cell recruitment and steroid production

Abstract: Factors that control recruitment of theca cells from ovarian stromal‐interstitial cells are important for early follicle development in the ovary. During recruitment, theca cells organize into distinct layers around early developing follicles and establish essential cell–cell interactions with granulosa cells. Recruitment of theca cells from ovarian stromal stem cells is proposed to involve cellular proliferation, as well as induction of theca cell‐specific functional markers. Previously, the speculation was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(59 citation statements)
references
References 60 publications
2
56
0
1
Order By: Relevance
“…According to other groups, thecal cells of antral follicles express both KITC mRNA and KIT protein (Motro & Bernstein 1993, Parrott & Skinner 1997, Driancourt et al 2000, Brankin et al 2004. Obviously, the KIT expression persists after ovulation in the theca-derived capsule/septum in (Parrott & Skinner 2000). Apart from vascular cells, the thecal layer consists of steroidogenic cells and fibroblasts, both of which are candidate cells for the small KITC cells in the bovine CL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to other groups, thecal cells of antral follicles express both KITC mRNA and KIT protein (Motro & Bernstein 1993, Parrott & Skinner 1997, Driancourt et al 2000, Brankin et al 2004. Obviously, the KIT expression persists after ovulation in the theca-derived capsule/septum in (Parrott & Skinner 2000). Apart from vascular cells, the thecal layer consists of steroidogenic cells and fibroblasts, both of which are candidate cells for the small KITC cells in the bovine CL.…”
Section: Discussionmentioning
confidence: 99%
“…Small luteal cells are likely candidates, because they are known to be derived from the theca where KIT transcription takes place (Driancourt et al 2000). In addition, isolated thecal cells secrete an increased amount of progesterone under KIT stimulation when compared with unstimulated controls (Parrott & Skinner 2000).…”
Section: Introductionmentioning
confidence: 95%
“…KITL receptors (c-kit) are present on oocytes and theca cells (Horie et al 1991, Manova et al 1993, Motro & Bernstein 1993. KITL acts to recruit thecal cells from surrounding ovarian stroma during the primordial to primary follicle transition (Parrott & Skinner 2000). How KITL interacts with AMH to regulate primordial to primary follicle transition is also examined in the current study.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the preantral to antral transition is most susceptible to follicular atresia. Several oocyte-and theca cell-derived factors promote granulosa cell proliferation and suppress apoptosis of granulosa cells, thereby preventing follicular atresia (Parrott & Skinner 2000, Orisaka et al 2009). It has been demonstrated that Effect of ovarian antibodies on mouse fertility oocyte-theca cell interaction also has a major role in folliculogenesis including activation of resting follicles, early growth, as well as terminal differentiation (Vanderhyden et al 1990, 1992, Eppig et al 2002, Matzuk et al 2002.…”
Section: Effect Of Ovarian Antibodies On Mouse Fertilitymentioning
confidence: 99%